In situ X-ray absorption spectroscopy study of CuO-NiO/CeO2-ZrO2 oxides: Redox characterization and its effect in catalytic performance for partial oxidation of methane - Toscani, Lucía María (2018)
In this work we analyze the effect of adding CuO to a NiO/Ce0.9Zr0.1O2 oxide by in situ X-ray absorption near-edge structure XANES technique in Ce L3, Ni K and Cu K absorption edges in terms of sample reducibility and catalytic activity. The oxidation states of Ce, Ni and Cu cations are followed up during temperature programmed reduction (TPR) experiments in diluted hydrogen and during catalytic tests for partial oxidation of methane (POM) reaction. Redox behavior was correlated to conventional fixed bed reactor results. The effect of firing temperature, crystallite size, CeO2-ZrO2 support and the presence of Cu and/or Ni as an active phase is also analyzed. Results showed a beneficial effect of CuO addition in terms of Ce and Ni reduction. A stronger interaction of NiO species with the support was revealed upon analysis of XANES reduction profiles in sample NiO/ZDC in contrast to bimetallic CuO-NiO/ZDC sample. Reduction onset temperature was found to depend on Ni crystallite size, being markedly promoted when samples exhibited low values of crystallite size both in supported and non-supported CuO-NiO species. In situ catalytic experiments for partial oxidation of methane showed a clear interplay between the redox behavior from the Ce in the CeO2-ZrO2 support and the Ni from the active phase. Sample NiO/ZDC exhibited a continuous reduction of Ce cations in CH4:O2 feed flow, carbon formation was detected in X-ray Powder Diffraction (XPD) patterns and Ni re-oxidation was found to take place, clear indications of catalyst deactivation. In contrast, sample CuO-NiO/Ce0.9Zr0.1O2 displayed a slight re-oxidation of Ce and no re-oxidation of Ni altogether with the suppression of carbon formation.